Pengaruh Lingkungan Kerja dan Motivasi Kerja terhadap Kinerja Karyawan di PT Argatama Multi Agung Bogor - ., Mulawarman; Firdaus, Muhamad Azis; Wibowo, Agung (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2026)
This study aims to examine the effect of the work environment and work motivation on employee performance at PT Argatama Multi Agung Bogor. A quantitative approach was employed using probability sampling with a proportionate stratified random sampling technique. The sample consisted of 105 employees selected from a population of 142 employees. Data were collected through questionnaires and analyzed using Structural Equation Modeling based on Partial Least Squares (PLS-SEM) with the assistance of SmartPLS 4.0 software. The findings indicate that the work environment has a positive and significant effect on both employee performance and work motivation. Work motivation also has a positive and significant influence on employee performance, although the strength of the effect is relatively weak. However, work motivation is not able to significantly mediate the relationship between the work environment and employee performance. These results imply that the work environment plays a more dominant role in improving employee performance compared to work motivation, highlighting the importance of creating a supportive and conducive work environment to achieve optimal organizational outcomes.